2016
DOI: 10.1039/c6ta02490d
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-free perovskite films by instant crystallization for efficient solar cells

Abstract: Ethyl acetate (EA) is introduced in a one-step spin-coating method and can induce instant crystallization of perovskite films to create efficient thermal annealing-free perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 39 publications
1
68
0
Order By: Relevance
“…We proposed that the strong interaction between PB2T‐SO and PbI 2 may form MAI‐PbI 2 ‐PB2T‐SO complex at GB, which not only results in small grains but also acts as defects to quench excited perovskites, leading to poor performance and severe hysteresis. It coincidentally agree with the previous work reported that the residue DMSO in perovskite film could decrease device efficiency . We further measured the dark current of three HEMs based devices (Figure S10, Supporting Information).…”
Section: Introductionsupporting
confidence: 91%
“…We proposed that the strong interaction between PB2T‐SO and PbI 2 may form MAI‐PbI 2 ‐PB2T‐SO complex at GB, which not only results in small grains but also acts as defects to quench excited perovskites, leading to poor performance and severe hysteresis. It coincidentally agree with the previous work reported that the residue DMSO in perovskite film could decrease device efficiency . We further measured the dark current of three HEMs based devices (Figure S10, Supporting Information).…”
Section: Introductionsupporting
confidence: 91%
“…Although, interesting attempts to form perovskite crystal without thermal annealing were carried out in recent years, film quality and device performance of state of the art devices are still largely relying on this approach. [113,114] The manipulation of process variables, including annealing temperature, duration time, temperature rise profile and substrate preheating offers an opportunity to optimize perovskite thin-film by controlling crystalline nucleation and growth kinetics. Summary of the performance of perovskite solar cells based on various crystallization methods is presented in Table 3.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…Recently, there are several reports appeared on cation combinations such as FA and Cs and/or MA perovskite formulations to yield black photoactive perovskite phase without annealing [8,9] . PSCs have been prepare at RT with efficiency of 15-17% [10,11] . However this method involves replacing the high boiling point dimethyl formamide (DMF) or dimethyl sulfoxide (DMSO) by a volatile solvent, which is not attractive from the practical point of view.…”
mentioning
confidence: 99%